Food Allergy and Philagrine Mutation in Children with Atopic Dermatitis - Duyuler Ayçin, Gülşah (European Journal of Therapeutics, 2021)
Objective: To determine the frequency and type of food allergy in patients having atopic dermatitis and to show the presence of mutations genetically. Methods: Patients diagnosed as having atopic dermatitis according to the Hanifin Rajka criteria were evaluated retrospectively. Eosinophils, total immunoglobin E, milk-specific immunoglobulin E, egg-specific immunoglobulin E, wheat-specific immunoglobulin E, and filaggrin gene mutation results were recorded. Nutrient elimination was performed for 1 month in patients who were thought to have food allergy owing to skin prick test and milk-specific immunoglobulin E results. The diagnosis was confirmed through a food loading test for the patients who benefited from the elimination. Results: Of the 66 patients included in the study, 42 (63.63%) were male. Food allergies were detected in 40 patients (60.6%). According to the Scoring of Atopic Dermatitis index, 9 out of 16 patients aged 40 years and over had food allergy and 31 out of 50 patients aged under 40 years had food allergy. There was no significant difference between the groups (P=.56). All patients included in the study were examined for filaggrin. Only 1 patient with a Scoring of Atopic Dermatitis index below 40 and milk allergy was found to have p.R501 * and c.2282-2285delCAGT mutations. Conclusion: Atopic dermatitis food allergy was found to be 60.6%. The most common improvement was egg allergy and egg elimination. There was no difference between atopic dermatitis severity and food allergy and laboratory tests. Severe atopic dermatitis was found to be 24.2%.